410 Romanian Managers’ Opinion Regarding the Place and Role of the Organizational culture in the Sustainable Development Management - H. C. Ion PETRESCU (Revista de Management Comparat International, 2011)
In the sustainable development management, the following important elements are present and operate: rules of conduct, values, aspirations and expectations, beliefs, specific myths, learned behavior patterns, habits, visible symbols of the company, motivation / reward systems, rights and obligations, components of the organizational culture. These generate the way the activities of sustainable development are structured. The organizational culture influences the sustainable development at the economic, social and environmental level. It contains sustainable values for change, oriented towards the sustainable development management.